The conservation status of Niugini black bass: a world‐renowned sport fish with an uncertain future. (2nd February 2016) - Sheaves, M.; Baker, R.; McLeod, I.; Abrantes, K.; Wani, J.; Barnett, A.
Abstract: The Niugini black bass, Lutjanus goldiei Bloch, is an estuarine and freshwater fish species endemic to New Guinea and the surrounding islands. It is the focus of a growing sport fishing industry that has the potential to provide long‐standing benefits to local people. Plantation agriculture, mining and logging are expanding in many catchments where L. goldiei is found, creating the potential for these industries to impact on L. goldiei and the environments it relies on. Understanding of the current status of the species, including its biology, ecology and distribution, is essential for its sustainable management. However, very little is known about the species. Here, the published literature, unpublished data and interviews with anglers and fisheries officers were used to draw together existing knowledge, assess the current conservation status, make a preliminary analysis of threats and identify key areas for research that will support the sustainable development of the L. goldiei sport fishing industry while fostering positive conservation outcomes.